Treatment of malignant pleural mesothelioma: current status and future directions. (July 2011) - Zucali, Paolo Andrea; De Sanctis, Rita; De Vincenzo, Fabio; Simonelli, Matteo; Lorenzi, Elena; Perrino, Matteo; Santoro, Armando
Malignant pleural mesothelioma (MPM) is an aggressive tumor, with a poor prognosis and an increasing incidence as a result of widespread exposure to asbestos. Approximately 80% of MPM can be attributed to asbestos fiber exposure. Surgery and radiotherapy have a limited role in highly selected patients and systemic therapy is the only potential treatment option for the majority of patients. Unfortunately, despite some definite activity of the novel antifolates such as pemetrexed and raltitrexed, the results even in combination with platinating agents are still modest. The median survival of these patients remains of approximately 1 year. Improvements in surgical and radiotherapy techniques, in tumor assessment and staging and in the knowledge of the major molecular pathways involved in MPM are needed to increase the survival of these patients.